The Trehalose-6-Phosphate Synthase and Trehalose-6-Phosphate Phosphatase in Cocoa (Theobroma cacao L.): Genome-Wide Identification and Expression Analysis - Nguyen, Quy Phuong; Cao, Phi Bang; Chu, Ngoc Thi Bich; Tran, Lan Thi Mai; Le, Man Thi; Luong, Hang Thi; Le, Quynh Thi Ngoc; Dong, Gioi Huy; Chu, Ha Duc (Bogor Agricultural University, Indonesia, 2025)
Cocoa (Theobroma cacao L.), a vital industrial crop renowned for its economic and nutritional significance, faces increasing challenges due to climate change-induced stresses. To enhance the understanding of cocoa's adaptive mechanisms, a comprehensive analysis was conducted on the trehalose-6-phosphate phosphatase (TPP) and trehalose-6-phosphate synthase (TPS) gene families, which play crucial roles in plant stress responses and development. Five TcTPP and eight TcTPS genes were identified using the latest cocoa genome assembly, distributed unevenly across nine of the ten chromosomes. Detailed physicochemical characterization revealed significant variability in amino acid length, molecular weight, isoelectric point, and hydrophilicity among these proteins, suggesting functional diversity. Phylogenetic analyses, performed using the maximum likelihood method, classified the TcTPP family into three distinct clades and the TcTPS family into two main groups. Gene structure examination uncovered variations in exon-intron organization, with TcTPP genes containing nine to twelve exons and TcTPS genes ranging from three to eighteen exons, indicating structural diversity within these families. Based on publicly available datasets, expression profiling demonstrated differential expression patterns of TcTPP and TcTPS genes during embryo development and under biotic stress conditions, such as pathogen infection by Phytophthora megakarya. Certain genes exhibited significant upregulation or downregulation in response to stress, implicating them in cocoa's defense mechanisms. Taken together, this study provides valuable insights into the TPP and TPS gene families in cocoa. It lays a foundation for developing strategies to enhance stress tolerance and sustainability in cocoa cultivation amidst changing climatic conditions.